A linear‐to‐circular polarization converter based on a bi‐layer frequency selective surface. Issue 7 (23rd March 2019) - Lin, Baoqin; Guo, Jianxin; Lv, Lintao; Wu, Jing; Liu, Zhe; Huang, Baigang
Abstract: In this work, a wideband linear‐to‐circular polarization converter is proposed based on a bi‐layer band‐pass frequency selective surface (FSS), whose unit cell consists of two layers of identical patterned metal films mounted on the two sides of a homogeneous dielectric layer, and the geometric pattern of each metal film is a square loop aperture surrounding a concentric square corner‐truncated patch. Both measured and simulated results show that the polarization converter can realize linear‐to‐circular polarization conversion in the frequency range from 6.87 to 10.07 GHz, which corresponds to a fractional bandwidth of 37.8%; moreover, its response is almost independent of the polarization and incidence angle of the incoming wave. Compared with published designs, the proposed polarization converter has a simpler geometry but a wider bandwidth, higher transmittance and better stability, it may possess potential applications in the design of CP antennas.